2006
DOI: 10.1111/j.1600-0536.2006.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive patch test reactions to allergens of the dental series and the relation to the clinical presentations

Abstract: The clinical manifestations of contact allergic dermatitis to dental materials are not uniform. This study was performed to detect the frequent allergens in the dental series associated with contact dermatitis and to define the causal relationship between the different allergens and the relevant clinical presentations. Between the years 2000 and 2004, 134 patients, aged 20-80 years, were patch tested. 121 patients were included in the study. The most frequent oral manifestations were cheilitis and perioral der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 28 publications
4
74
2
3
Order By: Relevance
“…Th us, Khamaysi et al included dental personnel with hand dermatitis in the research of contact allergic reactions, but only 39% of them were positive on patch test, mostly to metals, i.e. nickel, gold, palladium and cobalt 31 . It was shown that hand dermatitis in dental workers is relatively commonly caused by metal allergies, although it is possible that dental instruments alone are not the only source of activation but rather a key factor in the occurrence of CD 31 .…”
Section: Reactions To Other Substancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Th us, Khamaysi et al included dental personnel with hand dermatitis in the research of contact allergic reactions, but only 39% of them were positive on patch test, mostly to metals, i.e. nickel, gold, palladium and cobalt 31 . It was shown that hand dermatitis in dental workers is relatively commonly caused by metal allergies, although it is possible that dental instruments alone are not the only source of activation but rather a key factor in the occurrence of CD 31 .…”
Section: Reactions To Other Substancesmentioning
confidence: 99%
“…Metals were, therefore, next to latex, another common potential cause of contact allergic dermatitis 31,32 . Th us, Khamaysi et al included dental personnel with hand dermatitis in the research of contact allergic reactions, but only 39% of them were positive on patch test, mostly to metals, i.e.…”
Section: Reactions To Other Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Among restorative materials, amalgam is the most common dental material that induces hypersensitivity reactions of oral mucosa. 1,2 The mercury component of the alloy has been mostly held responsible for adverse immunological effects, with occasional reactions to other components such as copper, tin or zinc. 1,2 Hypersensitivity reactions to mercury associated with amalgam restorations comprise an array of clinical manifestations on oral mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The mercury component of the alloy has been mostly held responsible for adverse immunological effects, with occasional reactions to other components such as copper, tin or zinc. 1,2 Hypersensitivity reactions to mercury associated with amalgam restorations comprise an array of clinical manifestations on oral mucosa. The most common type presents as a lichenoid reaction which involves a delayed, type IV and cell-mediated hypersensitivity response.…”
Section: Introductionmentioning
confidence: 99%